Vũ Hồn có phải là người họ Vũ đầu tiên ở Việt Nam - Khôi, Vũ Thế (VNU Journal of Science: Social Sciences and Humanities; Vol 20 No 1, 2004)
There is a relatively popular opinion among researchers and writers on Vu family tree that, is all members of the exist ing Vu d a n in Vietnam originate from a progenitor namely Vu Hon who was a mandarin of the Duong dynasty, and whose country was Phuc Kien - China, dominating An Nam from 841 to 843 and then staying there. Based on information on Thanh Mai Bell discovered in 1986 in Thanh Mai commune, Thanh Oai district, Ha Tay province, there is contrary evident against the above opinion: On the Bell casted since 798, there carved a commander of the Am Binh district (the Cam Tuc province at present) whoso surname was Vu, and who was a member of the Tuy Hy in Thanh Mai and used to taking part in carving the bell. As such, there had been person having Vu surname there before Vu Hon in An Nam. The opinion " Vu Hon - the sole progenitor” resulted in situation "continuation", inevident connection of the genealogies of the Vu clan, causing erroneousness of real picture of clan and devaluation of a family annals as an old material.